Holocene grinding stones at Madjedbebe reveal the processing of starchy plant taxa and animal tissue. (February 2021) - Hayes, E.H.; Field, J.H.; Coster, A.C.F; Fullagar, R.; Matheson, C.; Florin, S.A.; Nango, M.; Djandjomerr, D.; Marwick, B.; Wallis, L.A.; Smith, M.A.; Clarkson, C.
Abstract: The functional study of ground stone artefacts and the analysis of charred plant remains together demonstrate that plant foods played a significant role in the diets of Aboriginal Australians through all occupation phases at the Pleistocene-aged archaeological site of Madjedbebe. Here we report studies of three sandstone grinding stones from the Holocene levels of the site, one associated with a radiocarbon age of 690 cal. BP, and the others with an age of 8320 cal. BP. The functional analyses involved technological studies combined with brightfield microscopy, starch grain analysis, biochemical testing and gas chromatography-mass spectrometry (GC–MS). All three tools had usewear consistent with plant processing, with two having abrasive smoothing and polish characteristics typical of seed-grinding. Significant quantities of starch were recovered from each artefact and demonstrate the early Holocene processing of waterlily ( Nymphaea violacea) and possibly kapok bush root ( Cochlospermum fraseri), cheeky yam ( Amorphopallus galbra) and long yam ( Dioscorea transversa) . In addition to starchy plant foods, one of the tools was used for processing animal tissue, as indicated by biochemical testing and GC–MS analysis, inferring a multi-functional use.